Sudan : 2003 Article IV Consultation and First Review of the 2003 Staff-Monitored Program-Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The discussions focused on reviewing the reforms that were implemented since the last consultation, policies for the remainder of the year as well as the parameters of the 2004 program, and the medium-term outlook. Executive Directors encouraged the exchange and monetary systems, but additional efforts are needed on the fiscal front. Finally, a progress was achieved in preparing a medium-term economic program that will be underpinned by the preparation, for the first time, of a three-year rolling medium-term budget (MTB).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet